La manifestación discursiva de la reflexión - González, Vicenta; Atienza, Encarna; Tomàs Pujolà, Joan (Linguarum Arena, 2015)
This article describes the communicative functions that can be identified in the discourse of language teacher training reflective portfolios. The ultimate goal is to describe possible clues to help develop reflective discourse of future users of teacher training portfolios. The study analyses a corpus of different Spanish teacher training portfolios that share a similar approach and structure. The results suggest that the reflexive discourse is manifested through various communicative functions. These are not manifested in correlative phases, but can appear in an amalgam of several communicative functions, some of which, however, may stand out by their frequency and level of explicitness.